Investigating How Cu Addition Affects the Gas Sensing, Electrical, Optical and Structural Properties of ZnO Nanoparticles - Fatemeh Moosavi; Giovanni Neri (Nanochemistry Research)
In this study, we report the morphological and microstructural characteristics (phase, crystallinity, morphology, surface functional groups) as well as the optical, electrical and gas sensing properties of pristine ZnO and Cu-doped ZnO nanoparticles prepared by a simple sol-gel method. Field Emission scanning electron microscopy (FE-SEM) showed that the nanoparticles were well synthesized, and their size was in the nanometer range. X-ray diffraction analysis of the synthesized nanoparticles displayed a hexagonal wurtzite crystalline arrangement with a grain size distribution of 21.2 nm for the pure- and 17.5 nm for Cu doped-ZnO. The FT-IR spectra showed a successful substitution of Cu ions in the ZnO lattice. The UV-vis spectroscopy exhibited a red shift in the absorption edge, indicating that the band gap energy decreased from 3.37 to 3.26 eV with Cu doping. The gas sensing nanoparticles were tested for their ability to detect ethanol and acetone in air at different temperatures. The results showed that the pristine ZnO gas sensor displayed a greater response to both gases at the low concentration of 10 ppm. On the basis of the obtained results, the fundamental sensing mechanism on these sensors is discussed in detail.